KOORDINASI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN KARO DENGAN DINAS SOSIAL DALAM PENANGGULANGAN BENCANA ERUPSI GUNUNG SINABUNG - Figlia Forlana Sigit; Simson Ginting (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
The occurrence of a natural disaster in an area is unavoidable. One great example of a natural disaster in Sumatera Utara is the eruption of Mount Sinabung. When a disaster occurs, it is necessary to carry out countermeasures, therefore the management of the Mount Sinabung eruption disaster is carried out by several agencies, one of which is coordination between the Karo Regency Regional Disaster Management Agency (BPBD) and the Karo Regency Social Service. This study shows the Karo Regency Regional Disaster Management Agency (BPBD) coordinates with the Karo Regency Social Service in dealing with the Mount Sinabung eruption disaster. The research method used is descriptive with a qualitative approach. Data collection was carried out through interviews, observation and documentation. The data obtained were then analyzed qualitatively using the Handayaningrats Coordination Theory. From the research results, it can be seen that the coordination of the Regional Disaster Management Agency (BPBD) with the Karo Regency Social Service in dealing with the Mount Sinabung eruption disaster still needs to be improved and improved. In terms of Relocation probem when before or after the Eruption occurred but it looks still lacking of communication between the Regional Disaster Management Agency (BPBD) of Karo Regency and the Karo Regency Social Service regarding their respective roles or tasks, the slow process of disaster management was caused by limited funds which resulted in the community not being aware of any assistance in Relocation during the Erupstion of mount Sinabung.